Chromogenic in-situ hybridization technique for the detection of porcine circovirus 3 in formalin-fixed paraffin-embedded lung and lymphoid tissues - Tan, Chew Yee; Lee, Kah Chun; Chiou, Ming-Tang; Lin, Chao-Nan; Ooi, Peck Toung (Veterinary World, 2023)
Background and Aim: Porcine circovirus 3 (PCV3) was recently reported in Malaysian commercial pig population in 2020 by conventional polymerase chain reaction (PCR), revealing a molecular prevalence of 17.02 in the sampled domestic pig population. This study aims to describe a chromogenic in situ hybridization (ISH) technique using digoxigenin (DIG)- labeled cloned PCV3 open reading frame 1 (ORF1) fragment DNA to detect and localize the PCV3 antigen in formalinfixed, paraffin-embedded lung, and lymphoid tissue specimens. Materials and Methods: Since PCV3 was mainly detected in lung and lymphoid tissues, we obtained tissue specimens from these organs from the previous Malaysian PCV3 study. Digoxigenin-labeled ISH probes were designed to target a 69 bp region of PCV3 ORF1 spanning from the nucleotide positions (282“350). Results: Light microscopy analysis revealed that chromogenic staining of PCV3 antigens was visualized within the cytoplasm of pneumocytes and lymphocytes, indicating positive ISH results. The results of molecular detection of PCV3 using PCR and ISH showed a high agreement of 90.91, including for the negative PCV3 status for all samples. Conclusion: This study reports a chromogenic ISH technique using DIG-labeled probes targeting PCV3 ORF1 to detect PCV3 antigens in lung and lymphoid tissues. Despite the limited availability of PCV3 antibodies, ISH remains relevant for investigating PCV3 replication and pathogenesis and can be used complementarily with PCR for evaluating the localization of antigens in infected tissues.